Advancing Human Assessment: The Methodological, Psychological and Policy Contributions of ETS - Bennett, Randy E.; von Davier, Matthias (Methodology of Educational Measurement and Assessment, 2017)
Educational Testing Service (ETS); large-scale assessment; policy research; psychometrics; admissions tests